Human infection with Seoul orthohantavirus in Korea, 2019. - Changmin Kang; Jin Il Kim; Jungmin Lee; Seongman Bae; Min Jae Kim; Ki-Joon Song; Jin-Won Song; Sung-Han Kim; Man-Seong Park (Public Library of Science (PLoS), 2021)
Of various rodent-borne hantaviruses, Seoul orthohantavirus (SEOV) causes haemorrhagic fever with renal syndrome (HFRS), as does Hantaan orthohantavirus (HTNV). Given global-scale of cases of human infection with SEOV, it is of great clinical importance to distinguish SEOV from other HFRS-causing hantaviruses. In May 2019, a middle-aged patient who had lived in a suburban area of Chungcheong Province, Republic of Korea and enjoyed outdoor activities was transferred to Asan Medical Center in Seoul, Republic of Korea with HFRS; his symptoms included high fever and generalized myalgia. The rapid diagnostic test performed immediately after his transfer detected HTNV-specific antibodies, and the patient was treated accordingly. However, two consecutive IFAs performed at ten-day intervals showed no HTNV-specific immunoglobulin (Ig) G. During continuous supportive care, next-generation sequencing successfully identified viral genomic sequences in the patient's serum, which were SEOV and not HTNV. Phylogenetic analysis grouped the L, M, and S genes of this SEOV strain together with those of rat- or human-isolated Korean strains reported previously. Given global outbreaks and public health threats of zoonotic hantaviruses, a causative pathogen of hantavirus HFRS should be identified correctly at the time of diagnosis and by point-of-care testing.